Sacred symbols and hate speech: A forensic-pragmatic study of Panji Gumilang’s discourse - Anggrayni, Okta Diana; Pratita, Ina Ika; Nasrullah, Riki (Al-Lisan: Jurnal Bahasa, 2025)
Background: Hate speech targeting religious symbols in digital media has sparked complex legal and social debates. Public figures often disseminate ideological views that may violate religious norms and legal provisions. Aims: This study aims to identify the linguistic forms and pragmatic functions of directive and representative speech acts in Pandji Gumilang’s statements on the Zaytun Official YouTube channel, which were used as evidence in a finalised criminal case. Methods: A descriptive qualitative method was employed using a forensic pragmatic framework based on Searle's speech act theory. Data were drawn from the Indramayu District Court Verdict No. 365/Pid.Sus/2023/PN.Idm using purposive sampling. The analysis focused on speech forms, communicative functions, and violations of Leech's politeness maxims, specifically tact, agreement, modesty, and approbation. Results: The study found 12 speeches containing hate speech against religious symbols, consisting of four directive speeches and eight representative speeches. All data violates the principles of politeness, especially the maxims of wisdom, agreement, humility, and decency. Statements such as "Indonesia is a sacred land", "not the kalam of Allah", and "strange nasab descendants of the Prophet Saw. show the manipulation of language that functions as an ideological means and has a legal impact. Implications: Findings reveal that directive and representative speech acts serve as ideological tools undermining Islamic symbols and provoking legal action. This research highlights the utility of forensic pragmatics in examining how language functions as symbolic power and a medium for religion-based offences.